рiзнi структурнi стани розчинiв 4-метилпiридин–вода: вивчення адiабатичної стисливостi на частотi гiперзвуку - Sabirov, L. M.; Semenov, D. I. (Publishing house "Academperiodika", 2019)
The behavior of the adiabatic compressibility BS with variation in the temperature t and the concentration x in the aqueous solution of a nonelectrolyte is experimentally studied from the fine structure of the spectra of light scattering. The sign inversion of the derivative of the adiabatic compressibility with respect to the concentration dBS(x)/dx and temperature dBS(t)/dt is observed. In the temperature-concentration phase diagram, the inversion points determine the lines of transition from the solution structure characterized by a nondisturbed continuous network of hydrogen bonds to the disturbed one, and, further, to the structure with fragmentary network.